Phosphonoacetic Acid-Resistant Herpes Simplex Virus Infection in Hairless Mice - Klein, Richard J. (1975)
Phosphonoacetic acid (PAA)-resistant type 1 herpes simplex virus population was isolated by repeated passage of the virus in the presence of this inhibitor. Hairless mice infected percutaneously with the inhibitor-resistant or the parental inhibitor-susceptible virus were treated intraperitoneally with PAA and 9-β-d-arabinofuranosyl-adenine by using several different dosage schedules. Whereas 9-β-d-arabinofuranosyl-adenine was effective both in the PAA-susceptible and PAA-resistant herpes simplex virus-induced skin infection, PAA suppressed only the infection induced by the parental PAA-susceptible virus.